Simultaneous Determination of Three Diterpenoid Alkaloids by HPLC in Unprocessed and Processed Fuzi - Cheng, Hongxia; Zeng, Yongchi; Fang, Cuifen; Cheng, Weiming (Asian Journal of Chemistry, 2012)
An HPLC method was developed for the simultaneous determination of three diterpenoid alkaloids (mesaconitine, aconitine and hypaconitine) in unprocessed and processed Fuzi. The solid phase was Gemini C18 column with isocratic elution using 0.04 M ammonium acetate-acetonitrile as the mobile phase. The results of methodology all fit the analytical requirements and the recoveries were 95.8-103.4 %. Quantitative analysis of the three alkaloids showed that the contents of the alkaloids varied significantly. It was the first report that figured out the alkaloids quantitative differences in unprocessed and processed Fuzi and could provide a scientific and technical platform for setting up a quality control standard.